Novel CMOS-Compatible Athermal and Polarization-Insensitive Ring Resonator as Photonic Notch Filter - Francesco Dell'Olio; Donato Conteduca; Giuseppe Brunetti; Mario N. Armenise; Caterina Ciminelli (IEEE Photonics Journal)
A hybrid titanium dioxide/silicon rich nitride ring resonator with the unique feature of being simultaneously athermal and polarization-insensitive is reported for the first time to our knowledge. Although its potential application domain is extremely wide, the designed integrated microphotonic cavity, having a racetrack shape, is intended for notch filtering in a microwave photonic passband filter. A careful selection of the CMOS-compatible material system and an innovative design approach have allowed a very low dependence of the filtering shape on the input beam polarization and, simultaneously, a thermal drift of the resonance wavelength <1.5 pm/K. The numerically estimated Q-factor, free spectral range, and extinction ratio are compliant with the requirements of the selected application, being equal to 7.8 × 104, 4 nm, and 30.7 dB, respectively.